Financialization and Financial Crisis: Looking through the Lens of Commodity Fetishism. Issue 4 (2nd October 2018) - Basu, Pranab Kanti
ABSTRACT: In this 150th year of the publication of Capital, vol. 1, it is time that we reread the connotations of the rich archive of concepts in Capital to see the insights that they can provide into the modern world. We intend to revaluate his critique of commodity fetishism (CF) and read the mutation of this critique in the era of financialization and see what insights it can provide into this phenomenon and into financial crisis. In the first part, we construct a narrative of the changes in the post-Fordist era, laying particular emphasis on what has been called financialization. In this section we tell a story about the financial crisis that started in 2006, leading to what has been called The Great Recession . In the next part, we elaborate the concept and critique of CF and see how it grounds a radically different way of looking at the capitalist order compared to the mainstream or neoclassical narrative. In the last part, we examine how, in the process of understanding the changes of the post-Fordist era the critique of CF has to mutate. We examine the changes and try to understand the crisis by deploying the mutated critique of CF.